Islam folklore : the staff of prophet Moses (Musa) & the wizards of pharaoh - Vandestra, Muhammad ([Scribl], 2018)
"And We inspired Musa (Moses) (saying), 'Throw your staff', ' and behold! It swallowed up straight away all the falsehoods which they showed." (Al-A'raf: 117) Why is it that a garden is sometimes green and sometimes yellow? Why is it that the deserts are dry and the mountaintops are covered with snow? Why is it that the color of the sun is like fire when rising and like blood when setting? Why is it that the moon turns from a beautiful full moon to a slim crescent? There are so many 'whys' which I cannot find the answer for. All I know is that I was a plant, then I became an inanimate object and then I turned into an animal. I know that my last transformation, from an object to an animal, was one of Allah's great Miracles. To Musa I was only a staff but to Almighty Allah I was something totally different. The staff of Prophet Musa (Moses), that is me. I am the staff of Musa. I preceded the Prophet while walking ... I would raise high then fall down onto earth all the way along. I have no mind and I know nothing about "why" or "how". At first the sun used to provide me with greenness and elasticity, but when I died it gave me strength and solidity, how amazing! Death is supposed to be the end of power and strength for all beings, but for me it was the opposite. I was only a branch of a tree and when I died I became stronger. So, you see that death means the ultimate end of power for some beings and a newborn power for others. It is both simple and miraculous at the same time. When a branch of a tree dies, it is turned into a staff and a staff does not gain its solidity unless it is completely dead. That is how power is generated from death, the cessation of being, and this is only a modest sign of Allah's Omnipotence. I believe in Allah just like all the plants and all the inanimate objects do, though each of us glorifies Allah in his own special way. So, it is me the staff of Musa! The most famous staff of all, chosen to be in the hands of Allah's Messenger to Pharaoh